2020
DOI: 10.3390/cryst10121089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Structure of the Short LnSb2O4Br Series (Ln = Eu–Tb) and Luminescence Properties of Eu3+-Doped Samples

Abstract: Pale yellow crystals of LnSb2O4Br (Ln = Eu–Tb) were synthesized via high temperature solid-state reactions from antimony sesquioxide, the respective lanthanoid sesquioxides and tribromides. Single-crystal X-ray diffraction studies revealed a layered structure in the monoclinic space group P21/c. In contrast to hitherto reported quaternary lanthanoid(III) halide oxoantimonates(III), in LnSb2O4Br the lanthanoid(III) cations are exclusively coordinated by oxygen atoms in the form of square hemiprisms. These [LnO8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The major advantage of using oxotellurates(IV) as host material is the fact, that the doped cation has not to be excited directly (usually in a very small energetic range), but the excitation can also take place in the region of the broad O−Te charge‐transfer band and/or on the lone‐pair electrons at the Te 4+ cations, providing the so‐called “inorganic antenna effect” [55] . Therefore an enhanced luminescent efficacy is expected to be observed, just like in the case of the rare‐earth metal(III) oxoantimonate(III) bromides RE Sb 2 O 4 Br ( RE =Eu−Tb), [56] where Sb 3+ plays a similar role as its isoelectronic Te 4+ neighbour in the periodic system of the elements (PSE).…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage of using oxotellurates(IV) as host material is the fact, that the doped cation has not to be excited directly (usually in a very small energetic range), but the excitation can also take place in the region of the broad O−Te charge‐transfer band and/or on the lone‐pair electrons at the Te 4+ cations, providing the so‐called “inorganic antenna effect” [55] . Therefore an enhanced luminescent efficacy is expected to be observed, just like in the case of the rare‐earth metal(III) oxoantimonate(III) bromides RE Sb 2 O 4 Br ( RE =Eu−Tb), [56] where Sb 3+ plays a similar role as its isoelectronic Te 4+ neighbour in the periodic system of the elements (PSE).…”
Section: Discussionmentioning
confidence: 99%
“…Common for both structures, the Sb 3+ cations form c 1 -tetrahedral [SbO 3 ] 3À units with three oxygen atoms and the electron lone pair, but this is the only common feature, since in both structures they are linked differently to each other to achieve {[SbO 2 ] À } motifs. In YSb 2 O 4 Br, their arrangement is already known from the representatives RESb 2 O 4 Br (RE ¼ Eu-Dy), 3,[21][22][23] namely the linkage via two corners to form onedimensional innite chains according to the Niggli formula Since the yttrium cations are surrounded by oxidoantimonate layers, an energy transfer from these layers towards any cation doped on the yttrium site could be expected. This was veried via luminescence spectroscopy (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence studies of Eu 3+ -doped GdSb 2 O 4 Br and TbSb 2 O 4 Br showed efficient sensitization of the Eu 3+ emission, proving that Sb 3+ is an efficient sensitizer for Ln 3+ emission. For TbSb 2 O 4 Br, a remarkably high energy transfer from Tb 3+ to Eu 3+ was detected that led to a substantially increased Eu 3+ emission intensity, showing it can be an efficient red light-emitting material [4].…”
mentioning
confidence: 97%
“…All publications in this Special Issue are original contributions. Different materials doped with Rare Earth Elements are presented in the publications, among them nanoparticles of Zr 1-x Eu x O 2-0.5x [1], fluoridated hydroxyapatite [2], Bi 12 GeO 20 sillenite bulk crystals [3], GdSb 2 O 4 Br, TbSb 2 O 4 Br [4], and LuVO 4 [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation